Combined Laser Therapy PWS532NM And 1064NM - Kirill A.Novikov, Olga B. Tamrazova, Larisa S.Kruglova (International Journal of Advanced Science and Technology, 2020)
Relevance. Currently, capillary angiodysplasia laser therapy is a dynamically developing area of ​​aesthetic medicine, in which, until now, there is a number of controversial issues. Thus, there is no consensus about the maximum effective wavelength of laser irradiation, method of skin cooling, as well as to managing patients in the early rehabilitation period. Objective: To evaluate the efficacy and safety of the combined use of two types of 532 nm and 1064 nm laser irradiation with gel-sapphire cooling in order to destroy capillary angiodysplasias. Methods: The results of the combined laser therapy of capillary angiodysplasias in 36 patients were evaluated by the method of comparison and grouping. Results. In the course of treatment, combination of 532 nm long-pulse laser irradiation and 1064 nm submilisecond laser irradiation showed high efficiency regardless of the process localization and the size of the lesions. The use of the combined method is characterized by a favorable safety profile, as evidenced by the shortening of the rehabilitation period. Conclusion. The results of the treatment, in combination with the absence of pronounced side effects, such as the formation of bullae, crusts, cicatricial changes and pigment disorders in patients with 1-3 Fitzpatrick skin phototype, allow to recommend this technique as an option for treatment of capillary angioplasty.